2016
DOI: 10.1007/s00300-016-1969-z
|View full text |Cite
|
Sign up to set email alerts
|

The early birds and the rest: do first nesters represent the entire colony?

Abstract: Climate change studies have detected earlier spring arrival of breeding birds. However, first nest dates (date first nests were found), which commonly provide the metric for earlier arrival, can be biased by population size or sampling effort. Our aims were to determine if: 1) first nest dates and median nest date (date when at least 50 % of all females have nested) were equivalent predictors for the spring arrival and 2) first nest date or median nest date were related to nest numbers. We recorded first and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…This is possible because early breeders at our study site have a longer prelaying period and rely more on local resources for egg production than late breeders . Other studies also found individual adjustments in early breeders that laid earlier despite nonsignificant changes at the population mean (Ahola, Laaksonen, Eeva, & Lehikoinen, 2009;Goodenough, Hart, Stafford, & Elliot, 2011;Jónsson, Lúðvíksson, & Kaller, 2017). In contrast, laying date of late breeders was extended by up to 3 days over time.…”
Section: Laying Date and Tclmentioning
confidence: 86%
“…This is possible because early breeders at our study site have a longer prelaying period and rely more on local resources for egg production than late breeders . Other studies also found individual adjustments in early breeders that laid earlier despite nonsignificant changes at the population mean (Ahola, Laaksonen, Eeva, & Lehikoinen, 2009;Goodenough, Hart, Stafford, & Elliot, 2011;Jónsson, Lúðvíksson, & Kaller, 2017). In contrast, laying date of late breeders was extended by up to 3 days over time.…”
Section: Laying Date and Tclmentioning
confidence: 86%
“…We analyzed data from two high-latitude breeding colonies of common eider: Rif (Iceland, 65°N, 185-620 nests per year) and Longyearbyen (Svalbard, 78°N, 326-445 nests per year). The Iceland colony was monitored in years 1992-2013; nesting onset was defined as the day when at least one breeding female was observed (with 1 to 10 nests recorded at day of nesting onset during the long-term monitoring period of 20 breeding seasons, for details see Jónsson et al 2017). In Svalbard, a clearly defined nesting area was counted daily in seasons 2016-2019.…”
Section: Empirical Data: Breeding Synchrony Of Common Eidersmentioning
confidence: 99%
“…This is a recently established colony, where the first nest was found in 1972 (Snæbjörnsson 2001), with an initial increase to 608 nests in 2008 followed by a decline to 360 in 2017 (Jónsson & Lúðvíksson 2013, Jónsson et al . 2016, S. J. Lúðvíksson pers. comm.).…”
Section: Methodsmentioning
confidence: 99%
“…The Rif colony, at the outmost tip of the Snaefellsnes peninsula on the Icelandic mainland, is located on two man-made islets in a small freshwater lake (Jónsson & Lúðvíksson 2013). This is a recently established colony, where the first nest was found in 1972 (Snaebjörnsson 2001), with an initial increase to 608 nests in 2008 followed by a decline to 360 in 2017 (Jónsson & Lúðvíksson 2013, Jónsson et al 2016. This pattern is more complex than the regional trend, as colonies in the southern part of Breiðafjörður have typically shown a decrease in Common Eider numbers over the period 1968-2010 .…”
Section: Study Systemmentioning
confidence: 99%